Effects of Telenursing on the Management of Self-care Behaviors in Patients With Chronic Hypertension - Fatemeh Talebi; Ali Asghar Jesmi; Mohammad Hassan Rakhshani; Ali Tajabadi (Gonabad University of Medical Sciences, 2023)
Background: The high prevalence of hypertension worldwide and its severe effects on various body organs are major health concerns in every community. The present study aims to evaluate the effects of telenursing on the management of self-care behaviors in patients with chronic hypertension. Methods: This randomized clinical trial was conducted on two groups with a pretest-posttest. The sample population included 82 patients with hypertension referred to comprehensive urban and rural health service centers in Garme City, Iran who were initially selected via two-stage cluster sampling and allocated into two groups of intervention and control by permuted block randomization (six patients in each block). Data were collected using a demographic questionnaire, the hypertension self-care profile, and phone follow-up, which were completed at the beginning of the study. The patients received a two-hour training session. The intervention group was followed up (telenursing) for three months, and the control group received routine care. After the intervention, the self-care questionnaire in patients with chronic hypertension was completed by both groups. Data were analyzed with SPSS software, version 25 using the Mann-Whitney U test, paired t-test, and the analysis of covariance (ANCOVA). Results: Telenursing increased the mean score of a healthy diet by 1.3 units (P=0.04) and the score of disease management by 1.19 units (P=0.004). However, the intervention had no significant effects on weight (P=0.09), supervision of the awareness of food labeling (P=0.38), and medication regimen (P=0.62).  Conclusion: According to the results, it is recommended to use this method to manage the disease and dietary habits of patients with chronic hypertension.